(untitled) (Stamford Journal of Pharmaceutical Sciences, 2009)
The development of a UV Spectrophotometric method for simultaneous estimation of Ranitidine HCl and Naproxen involves absorbance measurement of Ranitidine HCl at 313 nm in pH 7.4 phosphate buffer and 314 nm in both 0.1N HCl and in water and that of Naproxen at 229 nm in pH 7.4 phosphate buffer and 232 nm in both 0.1N HCl and in water corresponding to the respective absorption maxima. Both the drugs obey Beer- Lambert’s law in the range of 5-25 Î¼g/ml for Ranitidine HCl and 0.2-1.25 Î¼g/ml for Naproxen. The method developed was validated to determine its linearity, precision, reproducibility and sensitivity. The tablet formulations were evaluated for the percent content of both the drugs at the selected wavelengths and the percent potency were 98.83 and 99.15 for Naproxen and Ranitidine HCl respectively. Key words: Naproxen, Ranitidine HCl, Ultraviolet spectroscopy, marketed products. doi:10.3329/sjps.v1i1.1781 Â S. J. Pharm. Sci. 1(1&2): 18-24